Heterogeneity of light availability and its effects on simulated carbon gain of tree leaves in a small gap and the understory in a tropical rain forest - Tang, Yanhong; Kachi, Naoki; Furukawa, Akio; Awang, Muhamad (Wiley, 1999)
To clarify the small-scale heterogeneity of light regimes in a rain forest, photosynthetic phoron flux density (PFD) was measured at 1-min intervals during six days at 12 microsites in each of two plots, a small gap and an understory in Pasoh Forest Reserve, Peninsular Malaysia. Frequency distribution of microsite PFD was unimodal with the peak value between 16 and 32 μmol/m2/sec in the small gap, but between 8 and 16 μmol/m2/sec in the understory. In the small gap, PFD was more variable among microsites; total daily PFD and daily sunfleck PFD exceeding 10 μmol/m2/sec tended to be higher (P< 0.05; t-test) compared to those in the understory. Sunfleck PFD exceeding 50 μmol/m2/sec, however, showed no difference between the two plots. Diffuse PFD transmittance, defined as the ratio of PFD in the forest to that measured at 43 m above ground during the periods 0800-0810 and 1750-1800 h, was significantly higher in the small gap than in the understory plot. Diffuse PFD transmittance was also positively correlated with microsite total daily PFD. To examine the effects of the subtle heterogeneity of light regimes on leaf carbon gain, we simulated carbon gain by sun and shade leaves in a typical shade-tolerant species, Brosimum alicastrum Sw. (Moraceae). Despite the similarity in total daily PFD, total daily carbon gain was considerably higher in the gap than in the understory for both sun and shade leaves. This study suggests that frequency distribution of PFD is critical in describing microsite PFD regimes and determining leaf carbon gain in the tropical forest floor.